Tingkat Kesadaran Keluarga terhadap Imunisasi Campak di UPT Puskesmas Sering Tahun 2025 - Elisabet Tarigan; Novita Simanjuntak; Kevin Habib Alhuda; Priskila Meilorika Daeli; Hellen Natasya Hia; Audra Debra Inestasia Tarigan (International Medical Journal Corp. Ltd, 2026)
Background: Measles is a dangerous contagious disease, especially for children, and can be prevented through immunization. However, measles immunization coverage in Indonesia has declined, including in the service area of UPT Sering Health Center , which experienced outbreak at the beginning of 2025 with 15 confirmed cases. Low family awareness—particularly the lack of support from husbands or other family members—has become one of the obstacles to immunization uptake. Objective: To determine the level of family awareness regarding the importance of measles immunization in the working area of the UPT Sering Health Center. Methods: This study uses a descriptive observational design with a cross-sectional approach. The population consists of all families with members suffering from measles, and the sample was taken using a total sampling technique. The instruments used were questionnaires on the level of public awareness of measles vaccination and family support, to assess knowledge and family support. Results: Out of 20 respondents, the majority were aged 36–45 years (45%), had a junior high school education (60%), and worked as housewives (60%). Most respondents had good knowledge about measles immunization (70%), but only 35% received good family support, while 40% received less support. Only 33.3% of respondents stated that their children had received the measles immunization. Conclusion: Although family knowledge was generally good, support for measles immunization remained low. The lack of support was influenced by religious beliefs, concerns about side effects, and low awareness of immunization importance. Educational efforts involving religious leaders and personal approaches are needed to increase immunization coverage.